The Effectiveness of Outdoor Study Method in Science Learning for Class V UPT SDN 198 Pinrang - Hatijah. N; Yunus Busa; Syawal Sitonda (Universitas Muhammadiyah Enrekang, 2024)
This research aims to analyze the effectiveness of the outdoor study method in learning Science for fifth-grade students in UPT SDN 198 Pinrang. The outdoor study method is a learning approach outside the classroom that provides direct experience for students to observe and understand science concepts contextually. This research uses a qualitative approach with field research methods, namely research carried out directly at the location to obtain the required data. Research subjects included class V homeroom teachers and students. Data was collected through observation, interviews and documentation techniques. The data analysis process is carried out in three stages, namely data reduction, data presentation, and drawing conclusions or verifying research results. The implementation of the Outdoor Study method in learning Natural Sciences in class V UPT SDN 198 Pinrang has proven to be effective, because the teacher uses an approach that is appropriate to the material and utilizes the surrounding environment as a learning medium.